2015
DOI: 10.14419/ijdr.v3i1.4363
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of developmental anomalies of teeth in a group of North Karnataka population, India

Abstract: <p><strong>Aims and objective:</strong> To assess the prevalence of the developmental dental anomalies like disturbances in size, shape, structure, eruption pattern and number in a group of North Karnataka population and to assess the dental anomalies in patients with head and neck syndrome.</p><p><strong>Method:</strong> A cross-sectional prospective survey was carried out at P.M.N.M Dental College and Hospital, Bagalkot, North Karnataka, India during the academic yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Our study observed a prevalence of 0.33% of this condition while Kayal et al 17 and Sener et al have reported a range of 0.03% to 1.5%. The incidence of Dens evaginatus in our study was 0.13% which is similar to the observation by Javali et al 10 The prevalence of dilaceration in our study was 0.03%, while Goya HA et al 18 observed a prevalence of 0.02% and Javali etal reported a prevalence of 1%.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study observed a prevalence of 0.33% of this condition while Kayal et al 17 and Sener et al have reported a range of 0.03% to 1.5%. The incidence of Dens evaginatus in our study was 0.13% which is similar to the observation by Javali et al 10 The prevalence of dilaceration in our study was 0.03%, while Goya HA et al 18 observed a prevalence of 0.02% and Javali etal reported a prevalence of 1%.…”
Section: Discussionsupporting
confidence: 90%
“…This is close to 0.93% as observed by Siddaih et al 11 and 0.58% as observed in the study by Prabhu et al 12 The presence of Talon's cusp may cause irritation of the tongue during Section: Dentistry function, compromise esthetics, occlusal interference may lead to cusp fracture, displacement of affected tooth, TMJ pain and traumatic bite. 12 The prevalence of Taurodontism (enlargement of tooth crown at the expense of root) was observed in 0.4% cases, which is close to 0.3% reported by Javali et al 10 and Sener et al 13 Supernumerary teeth or Hyperdontia is a freqent finding in dental practice and in our study it was found in 0.3% cases, which was similar to the findings of Deolia et al and close to 0.5% as observed by Salem G. 14 Most supernumerary tooth are impacted and usualy diagnosed incidentaly on radiographic examination. These may be asymptomatic or may cause tooth displacement and failure of eruption.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Impacted tooth is one of the most commonly occurring dental anomalies. Frequency varies depending on the source and study population: 4.5% of dental anomalies in modern population of North Karnataka, India [10], 19.2% in Jatt, Israel [22], 26.2% in Konya, Turkey [28], 56.5% in Bhopal, India [25], 48.3% in Ordu, Turkey [1], 69% in Singapore, China [26]. The most commonly impacted teeth are mandibular and maxillary third molars, followed by maxillary canines [6,22].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency varies depending on the source and study population (see the text for more details); here we present mean per cent of each type, standard deviation are in round brackets. Sources: [1,10,22,25,26,28].…”
Section: Introductionmentioning
confidence: 99%